2009
DOI: 10.1155/2009/912848
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Clearance of Hepatitis C after Liver and Renal Transplantation

Abstract: Spontaneous clearance of hepatitis C virus (HCV) is rare in immunocompromised patients, such as those who have undergone organ transplantation. It has been recognized that patients receiving liver transplantation for HCV-related disease have decreased graft and patient survival compared with those transplanted for other etiologies. There is a growing trend toward treating HCV recurrence aggressively after liver transplantation. For other organ transplant recipients with concurrent HCV, treatment is not often a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…It was also reported after liver transplantation for HCVehuman immunodeficiency virus (HIV) coinfected patient [11] as well as in patients with combined liver and kidney transplantation [12]. We report a case of spontaneous clearance of HCV genotype 4 after cadaveric liver retransplantation.…”
mentioning
confidence: 75%
“…It was also reported after liver transplantation for HCVehuman immunodeficiency virus (HIV) coinfected patient [11] as well as in patients with combined liver and kidney transplantation [12]. We report a case of spontaneous clearance of HCV genotype 4 after cadaveric liver retransplantation.…”
mentioning
confidence: 75%
“…Recognizing a lack of immediate post-transplant HCV testing in our series, we cannot definitely exclude early viremia with HCV clearance as a theoretical biological explanation for HCV seropositivity. However, donor derived HCV is typically associated with early and persistent viremia and accelerated HCV-related hepatic disease in the recipient [16]. Cases of spontaneous viral clearance and seroconversion have been reported, but are exceptional, occurring many years after transplant and in association with a reduction in immunosuppression [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Such an outcome has substantial implications when evaluating, for example, treatment strategies against HCV before and after liver transplantation in patients with advanced liver fibrosis [ 40 ]. It has been reported that spontaneous clearance of HCV after transplantation is rare while reinfection of the allograft is common; therefore reducing the prognosis of these patients [ 41 44 ]. Adopting antiviral drugs that could eradicate the virus from the bloodstream and reduce the risk of reinfection of the allograft could then potentially generate substantial savings in MRU-related costs and improve the condition of the patient.…”
Section: Discussionmentioning
confidence: 99%